math

posted by .

how do i solve this G(t)=4t+1 find the following G(2)=, G(-10)=, G(6.9)=

  • math -

    g(2) = 4(2) + 1 = 9
    just substitute the number in perinthases for t.

  • math -

    given the function G(t)=4t+1 find each of the following G(2)=, G(-10)=, G(6.9)= plz help me don't understand this

  • math -

    Subsitute the 2 for the t, and then the -10, then the 6.9 so you get:
    g(2) = 4(2) + 1 = 9
    g(-10) = 4(-10) + 1 = -39
    g(6.9) = 4(6.9) + 1 = 28.6

    :D

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. MATH PLEASEEEEE

    I have a question, if f(x)=x/2 and g(x)=3x+1 find: a) (f+g)(x) i know you go x/2+3x+1. but how do i solve that?
  2. Algebra

    15. A boat travels 30 miles upstream in 4 hours. The trip downstream takes 2.5 hours. Find the rate of the boat in still water. 33. Solve the following: (q + 2)^2 = 25 34. Solve the following: y^2 + 6y + 9 =49 39. How many real roots …
  3. Math

    Please help me solve this.. It costs $10 plus $8 per hour to rent a canoe. Brandon and Erin have $50. Solve the following equation to find how many hours they can rent a canoe. 8h +10 = 50
  4. math

    1.)Name the property that is illustrated. a) 7 „e 6 ƒ­ 6 „e 7 b) 7 ƒy (1 ƒy 9) ƒ­ (7 ƒyƒn1) ƒy 9 2.) a) Identify the base in the following statement b) Solve for the amount. What is 81% of 285?
  5. math

    solve the following: ax + by = a-b bx - ay = a+b find the value of x and y
  6. math

    1. solve the following inequality to find a range of values for x : -18 < x -7 < -6 2. solve the following inequality to find a range of values for x : -96 < -12x < -12
  7. Math

    Solve the following system: 4x-y+z=6 2x+y+2z=3 3x-2y+z=3 Find the values for x, y, and z
  8. Math

    Solve the following: 56 is ______% of 125 What number is 45% of 680?
  9. SAT math

    1. x>15-2x / -3 Solve the linear inequality. Write the solution in set builder notation. So, -3x>15-2x, x<-15..?
  10. math

    Explain two ways that you can solve for R in the following division statement. Then, use one of your methods to find R. x^3+4x^2-3x=(x-1)(x^2+5x+2)+R could you divide x^3+4x^2-3x by (x-1) to get the quotion of (x^2+5x+2)+ the remainder …

More Similar Questions